Seroprevalence of Hepatitis E Among Hemodialysis Patients: A Report From Hamadan, Iran - Eini, Peyman (Hepat Mon, 2015)
BACKGROUND: Previous studies have documented a high prevalence of hepatitis E among patients undergoing maintenance hemodialysis. Available studies reporting on the seroprevalence of hepatitis E in hemodialysis patients in Iran, an endemic region for the disease, are sparse. OBJECTIVES: The present study aimed to determine the prevalence rate of anti-hepatitis E antibody in hemodialysis patients in Hamadan, Iran. PATIENTS AND METHODS: In this cross-sectional study, all 153 consecutive patients undergoing hemodialysis in two centers were enrolled. Patients’ demographic and clinical data were collected, using a standard questionnaire and from medical records. Serum immunoglobulin G concentrations against hepatitis E were determined using the enzyme linked immunosorbent assay method. RESULTS: Thirty patients (19.2%), were seropositive. Seropositive patients were not significantly different from seronegative patients, with regard to age, sex, level of education, access to filtered water, and duration and frequency of hemodialysis. The proportions of patients with hepatitis B, C, and HIV infection were comparable between the two groups. CONCLUSIONS: One in five patients undergoing maintenance dialysis in Hamadan is seropositive for hepatitis E immunoglobulin G antibody. Future studies are needed to investigate the factors contributing to the observed high prevalence rate and the possibility of parenteral transmission of hepatitis E.